PROSEDUR PEMERIKSAAN MAGNETIC RESONANCE IMAGING (MRI) LUMBAL DENGAN KASUS HERNIA NUKLEUS PULPOSUS (HNP) - Danil Hulmansyah; Marido Bisra (LPPM STIK Makassar, 2025)
Background: The lumbar vertebrae are the largest and strongest part of the vertebrae because the body weight increases towards the inner end column. Therefore, the lumbar vertebrae are a common site of injury and pathology. Aim: One of the lumbar disorders is Herniated Nucleus Pulposus (HNP). A lumbar nucleus pulposus hernia is a local displacement of the disc beyond the anatomical boundaries of the intervertebral space causing pain, weakness or numbness, and/or tingling in a myotomal or dermatomal distribution (Rusmayanti & Kurniawan, 2023). Methods: The research method used is descriptive qualitative with a case study approach. Results: Detection of HNP according to can be done using conventional radiology, myelography/using contrast media, CT scan, and MRI. Conclusion: Magnetic Resonance Imaging (MRI) is the gold standard for diagnosing HNP because magnetic waves can identify the location of HNP, as well as determine the nerve that is experiencing clamping. Keywords: MRI Lumbal, Hernia Nukleus Pulposus, Radiologi, Prosedur